How to select the best: Selection procedures of innovation agencies. Issue 3 (23rd June 2020) - Biegelbauer, Peter; Palfinger, Thomas; Mayer, Sabine
Abstract: Innovation agencies, that is organizations with the primary focus of funding applied research and technological development, evaluate project proposals to select the most promising proposals for funding. At the moment, there is only little verified knowledge available on project evaluation and selection processes of innovation agencies. We want to show how projects are evaluated and selected in these organizations. We want to also make a contribution for better understanding the variety of the utilized processes by pointing out the reasoning behind some of the most important practices. This article therefore focuses on the following questions: How are projects selected in innovation agencies? What are the employed procedures and practices? Are there differences in procedures and practices and what would be the reason for these differences? The basis for answering these questions is a study produced for the European Association of National Innovation Agencies, Taftie. There we have analysed the project selection procedures of 18 programmes run by 12 European innovation agencies. To do so, we have produced an overview of existing selection procedures of the innovation agencies, analysed, and compared the procedures along the stages of a typical selection process. The key points of interest were role of evaluators, selection criteria, ranking procedures, and general process issues.